The Quran was Revealed in Conversational Arabic - Shaker Amery (دراسات فی اللغه العربیه و آدابها, 2014)
Allah, because of His wisdom and omniscience chose Arabic as a framework and expression of His greatness and miracles. The multitude of Arabic dialects at the time of the revelation of the Quran has caused the scholars to disagree on the dialect in which the Quran was revealed. This study first discusses the status of Mecca and its Bazaars before Islam. Then, it explains some important terms: language, dialect, lingua franca, core language, and colloquial language. Arabic dialects were so similar at the time of revelation of the Quran there was a commonality of 90 percent. The existence of many dialects caused the spread of Arabic language. This could be seen in the compilation of rich and comprehensive dictionaries and grammar books. This article tries to prove that the dialect of revelation was not that of Qureish but a common one. It was the fluent dialect people conversed in it. Of course, some changes have happened to the language of the people. All reasons put forth claiming that the dialect of Qureish dominates the Quran are false, inexact and based on no proofs.